The Impact of Changing Technology of Motor Vehicles on Road Tax Revenue - Fullarton, Alexander (CCH Australia Limited, Monash University, 2018)
This paper considers the impact on road tax revenue of changes in the technology of motor vehicles. As the drive trains of motor vehicles are transformed from internal combustion engines to electric motors, their energy sources may transition significantly from taxable fossilfueltonon-taxablerenewableenergy. Revenuefrommotorvehiclefuelexciseslevied on petroleum products and allocated to the construction and maintenance of Australia’s roadways will decrease accordingly. Therefore, to continue to fund the road transport infrastructure, governments will be obliged to change their focus about how road tax revenue is raised. This paper considers the current number of electric vehicles (EVs) on Australian roads and attempts to predict the future uptake of EVs by road users up to the year 2035. It looks at the likely impact of reduced road tax revenue from motor vehicle fuel excises on future contributions by the Australian government for the construction and maintenance of Australian roadways. To that end, the paper examines data published by the Australian Bureau of Statistics (ABS) and statistics from the Australian Taxation Office (ATO). It also refers to sales data provided by motor vehicle manufacturers. It then compares the results of those examinations with data from a case study of a plug-in hybrid electric vehicle (PHEV) owned and operated by a solar project in rural Western Australia. The paper concludes that future revenue from fuel excises may decrease as a consequence of the introduction of EVs. However, as there has not been an official link between road tax revenue and road construction and maintenance expenditures since 1959, a reduction in road tax revenue will not necessarily affect funding for the construction and maintenance of Australian roadways.